Latihan Penguatan Scapula untuk Mengatasi Disfungsi Sendi Bahu Pasca Operasi Radical Mastectomy pada Dewasa Muda - Hanifah Dwi Nurma; Totok Budi Santoso (FORIKES, 2024)
Physiotherapy in post-radical mastectomy patients for breast cancer is generally performed to optimize post-operative injuries, including muscle strength, joint range of motion, so that they can return to normal activities. The purpose of this case report was to describe scapular strengthening exercises in the form of hold-relax exercises and exercises using dumbbells to improve shoulder joint dysfunction after mastectomy surgery. This study was a single case report, namely a 38-year-old female patient with post-radical mastectomy left stage 3 who has met the criteria, namely unilateral mastectomy, age less than 40 years, and first time experiencing cancer. Data were obtained through pain measurements with the Numeric Rating Scale (NRS), measurement of joint range of motion with Range of Motion (ROM), measurement of muscle strength values with Manual Muscle Testing (MMT), and measurement of functional ability with Quick DASH Outcome Measurement. The subject was given an intervention in the form of scapular strengthening exercises in the form of hold relax exercises and exercises using dumbbells. The exercises were carried out 4 times for 2 weeks. The results of the study showed that the degree of pain decreased from 6 to 3, shoulder flexor ROM increased from 1000 to 1650, muscle strength increased from 3 to 4, and the Quick DASH Outcome Measurement value decreased from 36 to 20. Furthermore, it was concluded that there were changes in patients towards the good, namely decreased pain, increased range of motion of the joints, increased muscle strength, and increased functional ability.Keywords: radical mastectomy; strengthening exercises; shoulder joint dysfunction; limited motion ABSTRAK Fisioterapi pada pasien pasca operasi radikal mastectomy pada kanker payudara secara umum dilakukan untuk tujuan optimalisasi cedera pasca operasi, termasuk kekuatan otot, lingkup gerak sendi, sehingga dapat kembali menjalani aktivitas normal. Tujuan dari laporan kasus ini adalah menggambarkan latihan penguatan pada scapula berupa latihan hold-relax dan latihan dengan menggunakan dumbbell untuk memperbaiki disfungsi sendi bahu pasca operasi mastektomi. Studi ini merupakan laporan kasus tunggal yakni seorang pasien wanita berusia 38 tahun dengan kondisi pasca operasi radical mastectomy sinistra stadium 3 yang telah memenuhi kriteria yakni mastektomi unilateral, usia kurang dari 40 tahun, dan baru pertama kali mengalami kanker. Data diperoleh melalui pengukuran nyeri dengan Numeric Rating Scale (NRS), pengukuran lingkup gerak sendi dengan Range of Motion (ROM), pengukuran nilai kekuatan otot dengan Manual Muscle Testing (MMT), dan pengukuran kemampuan fungsional dengan Quick DASH Outcome Measurement. Subjek diberikan intervensi berupa latihan penguatan pada scapula berupa latihan hold relax dan latihan dengan menggunakan dumbbell. Latihan dilakukan sebanyak 4 kali pertemuan selama 2 minggu. Hasil studi menunjukkan bahwa derajat nyeri menurun dari 6 menjadi 3, ROM fleksor shoulder meningkat dari 1000 menjadi 1650, kekuatan otot meningkat dari 3 menjadi 4, dan nilai Quick DASH Outcome Measurement menurun dari 36 menjadi 20. Selanjutnya disimpulkan bahwa terdapat perubahan pasien kearah baik yaitu penurunan rasa nyeri, peningkatan lingkup gerak sendi, peningkatan kekuatan otot, dan peningkatan kemampuan fungsional.Kata kunci: mastektomi radikal; latihan penguatan; disfungsi sendi bahu; keterbatasan gerak